Light and Electron-Microscopic Studies on the Tubal Tonsil of the Buffalo (Bubalus bubalis) - Girgiri, Ibrahim Alhaji; Kumar, Pawan (Journal of Buffalo Science, 2020)
The tubal tonsils of 12 adult buffaloes of the local mixed breed were studied using light and electron microscopy. The tonsillar mucosa lined by pseudostratified columnar ciliated epithelium with goblet cells was modified into lymphoepithelial, due to its association with underlying lymphoid tissue. The lymphoepithelial further modified into follicle-associated epithelium (FAE) characterised by absence of the ciliated cells, goblet cells and the presence of more lymphocytes. The FAE exhibited varying modifications and presented M-cells intimately associated with lymphocytes. At places, the change of the epithelium also showed the presence of specialised M-cell like cells without any association with lymphoid tissue. The lymphoid tissue was in the form of isolated lymphocytes, diffuse aggregations and follicles. The goblet cells of the respiratory epithelium and the glandular acinar cells showed positive activity for the different carbohydrate moieties like acidic and neutral mucopolysaccharides, glycogen, mucins, weakly sulfated acidic mucosubstances, hyaluronic acid and sialomucins. Scanning electron microscopy of the mucosal surface presented a dense mat of cilia, and the FAE exhibited a heterogeneous population of microvillus and M-cells. Transmission electron-microscopy demonstrated the different cell organelles of the various epithelia as well as the cellular profiles of the propria-submucosa, including the high endothelial venules where lymphocytes migration by both inter-endothelial and transvascular routes was also observed. The structural features of the tubal tonsil suggest that new strategies are required to explore this tonsil for targeted delivery of drugs and develop more effective vaccines by the intranasal route.